Attitudes toward interprofessional healthcare teams: A comparison between undergraduate students and alumni. Issue 3 (May 2013) - Makino, Takatoshi; Shinozaki, Hiromitsu; Hayashi, Kunihiko; Lee, Bumsuk; Matsui, Hiroki; Kururi, Nana; Kazama, Hiroko; Ogawara, Hatsue; Tozato, Fusae; Iwasaki, Kiyotaka; Asakawa, Yasuyoshi; Abe, Yumiko; et al.
<x xml:space="preserve">Abstract</x> The goal of effective interprofessional education (IPE) is high-quality patient-care delivery and attaining a high level of patient satisfaction in clinical settings. We aimed to examine if alumni who have studied in an IPE program at a pre-licensure stage maintain a positive attitude toward collaborative practice (CP) in the postgraduate clinical experience. This paper presents a cross-sectional descriptive study which employed the modified attitudes toward health care teams scale (ATHCTS) to examine the relationship between exposure to clinical practice and the attitudes toward interprofessional healthcare teams. Results indicated that the overall mean score of alumni was significantly lower than that of undergraduate students on the modified ATHCTS. Only "team efficacy" had a significantly lower regression factor score in alumni than undergraduate students. Our findings suggest that changes in professional identity in a team may be due to contact with patients after graduation in the postgraduate clinical healthcare experience. The reduction of attitudes toward healthcare teams in the postgraduate clinical experience may be related to "team efficacy". We emphasize the need for in-service IPE for sustaining attitudes and providing a useful CP, which results in good clinical outcome.